Anticancer and Antiinflammatory Effects of Bamboo Salt - Dr. Xin Zhao (Anticancer and Antiinflammatory Effects of Bamboo Salt, 2021)
As an inorganic substance, salt plays an important role in regulating the metabolism and permeability of muscle. It is said that in ancient times, food was eaten raw without additional salt intake, but in the process of cooking food, efforts were made to obtain salt. According to KS specification, salt is divided into natural salt and refined salt. Refined salt is again classified into mechanical salt and processed salt. Mechanical salt is mass produced by ion exchange, and processed salt is heated, including roasted salt and bamboo salt. Bamboo salt is different from common salt. It is rich in inorganic substances needed by human body. It has effects on various diseases. Related to this, it has therapeutic effects on gastritis, gastric ulcer, digestive system diseases, trauma treatment, detoxification. In addition, we also published the experimental results of toothpaste mixed with bamboo salt to reduce the number of Streptococcus in the mouth and relieve the symptoms of gingivitis. In this study, the physicochemical properties, antioxidant and anticancer functions of bamboo salt were studied. Bamboo salt particles are irregular and do not show obvious morphology, while natural salt is regularly observed in a variety of forms. The grain size of bamboo salt is about 10 times smaller than that of sea salt. In addition, although the crystal lattice of bamboo salt is distorted, the crystal lattice distortion can not be induced in the solar salt structure. Therefore, the crystallization and lattice distortion of bamboo salt means that the stable state energy of bamboo salt structure is in a higher state. Bamboo salt is a new material with higher energy state than sea salt and refined salt, which is considered to be completely different from ordinary salt. The DPPH antioxidant effect of bamboo salt was better than sea salt and refined salt, and the antioxidant effect of Rubus coreanus bamboo salt was better than 9 times bamboo salt. Through self salt directly inducing mutation causes and Ames test of MNNG, the results of anti mutation of Rubus coreanu bamboo salt and the 9 times bamboo salt appeared, and other salt had mutation effect. The in vitro anticancer experiment of bamboo salt is MTT method, using HCT-116 human colorectal cancer cells, HT-29 human colon cancer cells and AGS human gastric cancer cells. The results show that the anticancer effect of bamboo salt is 15% higher than that of sea and solar salt at 1% concentration. The in vitro anticancer effect of raspberry bamboo salt was better than that of 9 times bamboo salt. The effect of bamboo salt on the expression of Bax, Bcl-2, iNOS, COX-2 mRNA and protein expression was the best. In vivo metastasis test showed that raspberry bamboo salt and bamboo salt had anti-cancer function, while sea salt and solar salt had the effect of inducing cancer. The liver protective effect of CCl4 injection on Rubus coreanus bamboo salt in soy sauce was also involved in the defense effect on AST, ALT and LDH reduction. In addition, iNOS, COX-2, TNF-\(α\), IL-1\(β\) and other anti-inflammatory effects appeared. The gastric protective effects of HCl ethanol on raspberry bamboo salt, 9 times bamboo salt and 3 times bamboo salt were higher than those of sea salt and solar salt. Rubus coreanu bamboo salt had similar effects with omeprazole. However, the antioxidant, anticancer and anti-inflammatory functions of bamboo salt and Rubus coreanu bamboo salt are better than those of sea salt and solar salt, which need to be confirmed continuously.